(untitled) (Revista Direitos Humanos e Democracia, 2026)
This paper aims to investigate, through a doctrinal study, the multidimensional poverty, which consequently calls for the establishment of new protective standards. To this end, the investigation approaches poverty in multidimensional terms from the perspectives of capabilities and human rights. Methodologically, the study predominantly employs the deductive research method. Additionally, the bibliographic research technique was adopted. As a result, poverty is identified as an autonomous element of human rights violations, aligned with Goal 1 and its targets of the United Nations 2030 Agenda for Sustainable Development, which addresses the eradication of poverty in all its forms and everywhere.